The problem of Arab interpretation in the thought of Nasr Hamid Abu Zayd. - Zerouka, Mustapha (El Omda in Linguistics and Discourse Analysis, 2023)
Abstract : Through our writing of this article, we seek to take the reader’s hand in order to clarify the picture for him regarding the problem of the term interpretation in the Arab world, and we especially mention the Egyptian thinker Nasr Hamid Abu Zaid, where we will discuss the definition of the term interpretation in the West and among the Arabs, and we mention the most important problems of interpretation among the Arabs that Nasr Hamed Abu Zaid will summarize it for us.